Student voice in school reform? Desiring simultaneous critique and affirmation. Issue 3 (3rd May 2020) - Mayes, Eve
ABSTRACT: While 'student voice' is advocated as a means for school reform, studies of its enactment have noted how student voice can become a technology of governance. This article works with the perplexities of a four-year funded period of reform at one secondary school, where a 'student voice' initiative and a Positive Behaviour Interventions and Supports programme gradually entwined. Complementing and extending a Foucauldian account of power as productive, Deleuze and Guattari's desiring-analysis generates simultaneous accounts of governance, resistance and affirmation. Mapping what behaviour tokens did, and what was done with these tokens, does not undermine the importance of 'listening' to students' (and teachers') voices, nor the incisive potential of critique, but rather considers latent pathways out of present repetitious patterns of school governance. It is argued that working with these simultaneous movements of voice may foster more productive conversations about perplexing school reform processes.